(untitled) (GEON Journal (Management, Organizations and Business), 2017)
The study of the professions has gone through several historical moments, from conceptual to academic and with diverse approaches, from a critical social analysis, to the capitalist and at the moment to a state of knowledge that has scarcely been worked in Mexico, but that has served as a base for the path of the curriculum in Higher Education as a bridge between the profession and the graduate from the characteristics that emanate from it; Thus, from the point of view of the economic-administrative area, this research deals with. Alluding to the profession Agüero Aguirre, (2003) establishes characteristics of a context that determines the national and international environment of the demands of the administrator, to lead it to the path of the curriculum.